The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/mec.15767
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting fungal responses to wildfire across different ecosystem types

Abstract: Wildfire affects our planet's biogeochemistry both by burning biomass and by driving changes in ecological communities and landcover. Some plants and ecosystem types are threatened by increasing fire pressure while others respond positively to fire, growing in local and regional abundance when it occurs regularly. However, quantifying total ecosystem response to fire demands consideration of impacts not only on aboveground vegetation, but also on soil microbes like fungi, which influence decomposition and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 123 publications
2
12
0
Order By: Relevance
“…We also compared the relative abundance and species richness of saprotrophic, pathogenic, and mycorrhizal functional guilds among garlic mustard treatments and between sampling dates using FUNGuild (Nguyen et al, 2016) to assign functional guild to taxa. Assignments with “probable” or “highly probable” confidence scores were included, and in cases where taxa were assigned to more than one guild, mycorrhizal classification was given higher priority than pathogenic, which was given higher priority than saprotrophic guild (Smith et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We also compared the relative abundance and species richness of saprotrophic, pathogenic, and mycorrhizal functional guilds among garlic mustard treatments and between sampling dates using FUNGuild (Nguyen et al, 2016) to assign functional guild to taxa. Assignments with “probable” or “highly probable” confidence scores were included, and in cases where taxa were assigned to more than one guild, mycorrhizal classification was given higher priority than pathogenic, which was given higher priority than saprotrophic guild (Smith et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We do not observe that Douglas-firs facilitate oak colonization to the same extent, potentially due to stricter hostspecificity in Douglas-fir root fungal communities (Figure 4). Third, we observed significant but variable effects of fire on root fungal colonization (Figure 1), richness (Figure 2) and community structure (Figure 3), demonstrating that fire-driven shifts in soil fungal communities (Smith et al, 2021) translate to differences in root-associated fungal community assembly. In support of H3, we found negative effects of fire on fungal species richness with both Douglas-fir and oak when growing in Douglas-fir forest soil, and a negative effect of fire on root fungal colonization in oak seedlings in Douglas-fir forest soil.…”
Section: Df Forest Soilmentioning
confidence: 85%
“…We chose this distance because prior investigation of ectomycorrhizal fungi found that spatial autocorrelation was limited to approximately 3 m distance (Lilleskov et al, 2004). Moreover, a prior study in this system found that the minor influence of geography on soil fungal community composition relative to other predictors increased most rapidly among the shortest pairwise distances (Smith et al, 2021). This indicates that even small spatial distances between samples create differences in community composition that are large relative to the maximum potential impact of geography, minimizing the potential statistical challenge of spatial autocorrelation in this system.…”
Section: Field Sitementioning
confidence: 99%
“…We also compared the relative abundance and species richness of saprotrophic, pathogenic, and mycorrhizal functional guilds among garlic mustard treatments and between sampling dates using FUNGuild (Nguyen et al 2016) to assign functional guild to taxa. Assignments with “probable” or “highly probable” confidence scores were included and in cases where taxa were assigned to more than one guild, mycorrhizal classification was given higher priority than pathogenic, which was given higher priority than saprotrophic (Smith et al 2021).…”
Section: Methodsmentioning
confidence: 99%